Product development and quality of pharmacy compounded chenodeoxycholic acid capsules for Dutch cerebrotendinous xanthomatosis patients - Bouwhuis, Natalja; Jacobs, Bart A. W.; Kemper, E. Marleen (Frontiers in Pharmacology, 2023)
In 2017 the drug chenodeoxycholic acid (CDCA) became unavailable to Dutch patients with the rare inborn error of metabolism cerebrotendinous xanthomatosis (CTX). This was a direct result of a steep price increase after CDCA was authorized in the EU as an orphan drug. As a result, Dutch health insurance companies were unable to reimburse this drug and the availability of CDCA to patients with CTX was directly at risk creating an unmet medical need. CTX is characterized by juvenile cataract, tendon xanthomas, infantile-onset diarrhea, psychomotor retardation and progressive cerebellar ataxia. Treatment with CDCA, when initiated before neurological symptoms are present, can prevent the onset of neurological complications. To assure continuation of patient treatment with a high quality product, the hospital pharmacy of the Amsterdam UMC developed CDCA capsules as a pharmacy preparation. A simple and robust formulation was developed for capsules in a broad dose range of 35-250 mg, ensuring that both pediatric and adult patients can receive an exact dose tailored to their specific needs. Capsules are prepared manually on a small scale for the individual patient. To assure the quality of the product, product validation and stability studies were performed. The results show that the product complies with all specifications based on the requirements of the European Pharmacopoeia. The capsules contain the declared amount of CDCA,